Reinforcement learning an introduction - Sutton, Richard S. (MIT Press, 1998)
Presents the book "Reinforcement Learning: An Introduction," written by Richard S. Sutton and Andrew G. Barto and published by the Massachusetts Institute of Technology (MIT) Press in 1998. The book is a textbook targeted toward engineers and scientists in artificial intelligence, operations research, neural networks, and control systems. Examines a computation approach to learning from interaction with environment.
Keywords: Reinforcement learning.; Massachusetts Institute of Technology Press.; Cambridge (Mass.); elektronické knihy; electronic books